A study examining the impact of drug abuse resistance education (D.A.R.E.) and a comparison group in a rural setting - Roth, Carol Jean (My University, 1992)
ROTH, C. J. A study examininayion of the impact of drug abuse resistance education (D.A.R.E.) and a comparison group in a rural setting. MPH in Community Health Education, 1992, 112pp. (R. D. Duquette). This research examined the effectiveness of D.A.R.E. in a rural setting. A comparison (nonD.A.R.E.) group was utilized to strengthen the study. The total subject pool equaled 530 fifth and sixth grade students, with 312 subjects in the experimental group (D.A.R.E.) and 222 subjects in the comparison group. Both groups were evaluated regarding 12 variables over 3 time samples-pretest, post 1, and post 2. An instrument designed for this study measured the change scores of all Ss regarding the predetermined variables that were based on program objectives. Data analyses consisted of descriptive statistics, ANOVA with repeated measures, and Tukey-HSD multiple range tests. A predetermined significance level (p < .05) governed the rejection of the null hypotheses. Data indicated a significant relationship regarding self-esteem, refusal techniques, knowledge, positive alternatives, comfort level, prediction of future use, and attitude toward police officers. No significance regarding decision making skills, interpersonal skills, peer/parent influences, consequential thinking/risk taking skills, and actual alcohol and other drug use was uncovered.
Keywords: D.A.R.E. (Project); Drug abuse -- Prevention